Chinese Islam's understanding of Zhongxiao 忠孝: Jin Tian-zhu's 金天柱 Qing Zhen Shi Yi 清眞釋疑. Issue 2 (3rd April 2023) - Ryun, Lee Oh
ABSTRACT: The scholar Jin Tian-zhu (1690 ~ 1765) was a Muslim of the Hui 回 ethnic group in the Qing dynasty who adhered to Islamic traditions handed down from generation to generation. In Qing Zhen Shi Yi, Jin Tian-zhu attempts to combine Confucianism and Islam through a simple comparison of their rituals. Jin Tian-zhu expresses his respect for Allah by attesting Allah's existence and insisting that humans should obey Allah. He admits that in reality, besides Allah, the ruler is also clearly an object of loyalty. In addition, he asserts that it is basic propriety for Muslims to be filial to their parents and that the scope of practice of filial piety must also apply to their ancestors beyond their parents. Jin Tian-zhu further expands his view of zhongxiao 忠孝 by asserting that the ultimate Muslim interest is in renlun 人倫, which he believes must be rectified.